Highly dynamic force control for experimental vibration analysis with an electrodynamic shaker Hochdynamische Kraftregelung für die experimentelle Schwingungsanalyse mit einem elektrodynamischen Shaker - Lüke, Christopher; Trächtler, Ansgar (Forschung im Ingenieurwesen)
Abstract A new control method aims at the precise high dynamic control of the force signal for experimental vibration analysis, which is generated by an electrodynamic shaker. A bending beam is used as a nonlinear test object. A design and a surrogate model of the test rig are shown and parameterized based on test rig measurements. The force control algorithm using input/output linearisation is described and implemented in Matlab/Simulink for simulative validation studies. Conclusions drawn from the mathematical description of the problem as well as simulation results show that the design of the contact between shaker and test object is crucial to achieve a high control bandwidth and at the same time reduce the energy consumption of the shaker. This leads to the practical application using a novel damping contact element. Finally, experimental test rig results are presented which show a closed loop bandwidth of at least 250 Hz for sinusoidal excitation signals.

„Ich mag an mir …“ - Grimminger-Seidensticker, Elke (Die GRUNDSCHULZEITSCHRFT)

Cost Analysis for a Small-Scale Hybrid, Hydrogen-Based PV Energy System - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 41st European Photovoltaic Solar Energy Conference)

Analysis and Demand Side Management of East African Rural Microgrids: Modelling and Experimental study - Philipo, Godiana Hagile

Duale Ausbildungsqualität: Eine kritische Auseinandersetzung mit dem Forschungsstand vor dem Hintergrund neuer Bedarfe und Möglichkeiten - Deutscher, Viola; Abele, Stephan; Festner, Dagmar; Findeisen, Stefanie; Goller, Michael; Harteis, Christian; Rausch, Andreas; Seifried, Jürgen (bwpaed online)

Expulsion prevention in resistance spot welding of dissimilar joints with ultra-high strength steel: An analysis of the mechanism and effect of preheating current - Yang, Keke; El-Sari, Bassel; Olfert, Viktoria; Wang, Zhuoqun; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing Processes)
The widespread adoption of ultra-high strength steels, due to their high bulk resistivity, intensifies expulsion issues in resistance spot welding (RSW), deteriorating both the spot weld and surface quality. This study presents a novel approach to prevent expulsion by employing a preheating current. Through characteristic analysis of joint formation under critical welding current, the importance of plastic material encapsulation around the weld nugget (plastic shell) at high temperatures in preventing expulsion is highlighted. To evaluate the effect of preheating on the plastic shell and understand its mechanism in expulsion prevention, a two-dimensional welding simulation model for dissimilar ultra-high strength steel joints was established. The results showed that optimal preheating enhances the thickness of the plastic shell, improving its ability to encapsulate the weld nugget during the primary welding phase, thereby diminishing expulsion risks. Experimental validation confirmed that by employing the optimal preheating current, the maximum nugget diameter was enhanced to 9.42 mm, marking an increase of 13.4 % and extending the weldable current range by 27.5 %. Under quasi-static cross-tensile loading, joints with preheating demonstrated a 7.9 % enhancement in maximum load-bearing capacity compared to joints without preheating, showing a reproducible and complete pull-out failure mode within the heat-affected zone. This study offers a prevention method based on underlying mechanisms, providing a new perspective for future research on welding parameter optimization with the aim of expulsion prevention.
Keywords: Expulsion Resistance spot welding Finite element modelling Preheating Weldable current range Ultra-high strength steel

Steuerwettbewerb als Chance - Birnbaum, Kirsten; Heckemeyer, Jost H.; Linau, Annette; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Time perspectives and collaborative performance in creative tasks - Auer, Thorsten Fabian; Hoppe, Julia Amelie; Thommes, Kirsten (Journal of Organizational Effectiveness: People and Performance)
Purpose The relationship between variation in time perspectives and collaborative performance is scarcely explored, and even less is known about the respective mechanisms that lead to varying task performance. Thus, we aim to further the literature on time perspectives and collaborative performance, shedding light on the underlying behavioral patterns. Design/methodology/approach We report a quasi-experiment analyzing the impact of past, present and future orientation variation in dyads ( N = 76) on their quantitative and qualitative performance when confronted with a simple incentivized creative task with constraints. Subsequently, we offer a qualitative analysis of comments given by the participants after the task on the collaboration. Findings Results indicate that a dyad's elevation of past orientation and diversity in future orientation negatively affect collaborative performance. At the same time, there is a positive effect of elevation of future orientation. The positive effect is driven by clear communication and agreement during the task, while the negative effect arises from work sharing and complementation. Practical implications This study provides insights for organizations on composing individuals regarding their temporal focus for collaborative tasks that should be executed rapidly and require creative solutions. Originality/value Our study distinguishes by considering the composition of past, present and future time perspectives in dyads and focuses on a creative task setting. Moreover, we explore the mechanisms in the dyads with a substantial elevation of/diversity in future orientation, leading to their stronger/weaker performance.
Keywords: Organizational Behavior and Human Resource Management

Approach for the Reliable and Virtual Design of Mechanical Joints in an Uncertain Environment - Einwag, Jonathan-Markus; Goetz, Stefan; Wartzack, Sandro (DS 133: Proceedings of the 35th Symposium Design for X (DFX2024))

Train Once Apply Anywhere: Effective Scheduling for Network Function Chains Running on FUMES - Blöcher, Marcel; Nedderhut, Nils; Chuprikov, Pavel; Khalili, Ramin; Eugster, Patrick; Wang, Lin (Proceedings of the IEEE International Conference on Computer Communications (INFOCOM))

Die Netzwerkanalyse als Schulentwicklungsinstrument. Schulische Netzwerke für begabungs- und leistungsfördernde Schulentwicklung visualisieren und systematisieren. - Schwermann, Anna; Ellersiek, Annchristin; Kottmann, Brigitte (Wege der Begabungsförderung in Schule und Unterricht. Transformative Impulse aus Wissenschaft und Praxis.)

InferCool: Enhancing AI Inference Cooling through Transparent, Non-Intrusive Task Reassignment - Pei, Qiangyu; Wang, Lin; Zhang, Dong; Yan, Bingheng; Yu, Chen; Liu, Fangming (Proceedings of the 15th ACM Symposium on Cloud Computing (SoCC))

Professionalität und Menschlichkeit: Arzt-Patienten-Interaktionen in William Carlos Williams’ Kurzgeschichte „The Girl with a Pimply Face“ - Mildorf, Jarmila (Heilkraft der Literatur: Zur Bedeutung der Literatur für eine menschliche Medizin)

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Optimization of Design and Operation of a Digestate Treatment Cascade for Demand Side Management Implementation - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)

Modellierung kleinskaliger Trennapparate mit Strukturpackungen und der Scale-up mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Pöschmann, René; Müller, Steffen; Paschold, Jürgen; Brösigke, Georg; Repke, Jens-Uwe; Riese, Julia; Kenig, Eugeny Y.

Evaluationsergebnisse einer Interventionsstudie zur Reduktion akademischer Prokrastination und Förderung studentischer Gesundheit - Schneider, Tamara; Klingsieck, Katrin B.

The ProGRess-Training – Reduce procrastination to improve students’ health. An Intervention study. - Schneider, Tamara; Klingsieck, Katrin B.

Computer aided flow investigation of liquid agricultural wastes - Bernemann, Sören Antonius; Maćkowiak, J.F.; Maćkowiak, J.; Kenig, Eugeny (Chemical Engineering Science)